1989
DOI: 10.1021/bi00430a065
|View full text |Cite
|
Sign up to set email alerts
|

Oxidoreduction reactions involving the electrostatic and the covalent complex of cytochrome c and plastocyanin: importance of the protein rearrangement for the intracomplex electron-transfer reaction

Abstract: Horse heart cytochrome c and French bean plastocyanin are cross-linked one-to-one by a carbodiimide [Geren, L. M., Stonehuerner, J., Davis, D. J., & Millett, F. (1983) Biochim. Biophys. Acta 724, 62] in the same general orientation in which they associate electrostatically [King, G. C., Binstead, R. A., & Wright, P. E. (1985) Biochim. Biophys. Acta 806, 262]. The reduction potentials of the Fe and Cu atoms in the covalent diprotein complex are respectively 245 and 385 mV vs NHE; the EPR spectra of the two meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 29 publications
6
48
0
Order By: Relevance
“…In order to directly compare cross-linking results for physiological and nonphysiological CcP complexes, we have carried out identical cross-linking procedures in tandem on the CcP/yeast iso-1 ferricytochrome c pair and the CcP/horse ferricytochrome c pair. In view of other protein cross-linking work using EDC (Mauk & Mauk, 1989;Peery & Kostic, 1989;Zhou & Kostic, 1991; Matthews & Brittain, 1986), we have been careful to use appropriate controls so that valid comparisons can be made for cross-linking results with CcP and physiological and nonphysiological partners. The specific controls are described in subsequent sections.…”
Section: Noncovalent Complexesmentioning
confidence: 99%
“…In order to directly compare cross-linking results for physiological and nonphysiological CcP complexes, we have carried out identical cross-linking procedures in tandem on the CcP/yeast iso-1 ferricytochrome c pair and the CcP/horse ferricytochrome c pair. In view of other protein cross-linking work using EDC (Mauk & Mauk, 1989;Peery & Kostic, 1989;Zhou & Kostic, 1991; Matthews & Brittain, 1986), we have been careful to use appropriate controls so that valid comparisons can be made for cross-linking results with CcP and physiological and nonphysiological partners. The specific controls are described in subsequent sections.…”
Section: Noncovalent Complexesmentioning
confidence: 99%
“…A model of this ternary complex involving relative motion of Cr(NH&+, cytochrome c and plastocyanin would then explain why, on the NMR time scale, no plastocyanin residues are masked from the inorganic probe on complexation with cytochrome c. The proposal that plastocyanin and cytochrome c move relative to one another within the encounter complex, perhaps by making and breaking ion-pair bonds [41], is consistent with recent experimental and theoretical studies of protein-protein complexes which emphasise the dynamic nature of the interactions involved. Examples include electrostatic analysis of the cytochrome c/cytochrome b5 interaction [41], calculations of Brownian dynamics [42], and comparison of the covalent and electrostatic complexes formed by plastocyanin and cytochrome c [43]. In the last of these studies, it was found that, when cross-linked, the proteins are 'locked' in unproductive orientations (i.e.…”
Section: Plastocyanin Interaction Surfacementioning
confidence: 99%
“…Studies of the cytf-PC reaction in vitro have suggested a substantial role for electrostatic interactions between the reactants (Morand et al, 1989;He et al, 1991;Modi et al, 1992a,b;Kostic, 1992, 1993;Meyer et al, 1993;Gross, 1993;Wagner et al, 1996;Kannt et al, 1996). Electrostatic effects were also observed in reactions of PC with different cytochromes (e.g., Peery and Kostic, 1989;Bagby et al, 1990b;Nordling et al, 1990;Roberts et al, 1991; Peery et al, 1991;Meyer et al, 1993;Qin and Kostic', 1996) and with photosystem I (Haehnel et al, 1994;Farah et al, 1995;Sigfridsson et al, 1996;Drepper et al, 1996). The structural data show the existence of two patches of negatively charged residues on the PC surface, viz., Asp-42 and -44, and, for the second patch, Glu-59 and -60 and Asp-61 (Guss and Freeman, 1983; domains.…”
Section: Introductionmentioning
confidence: 99%